Livestock sustaining intensive smallholder crop production through traditional feeding practices for generating high quality manure-compost in upland Java - Tanner, J.C.; Holden, S.J.; Owen, E.; Winugroho, M.; Gill, M. (2001)
Information is needed on the biophysical and economic rationale for labour-demanding (and therefore, expensive) backyard animal rearing systems on smallholdings in the uplands of Java where livestock have been an integral part of highly intensive agriculture for centuries. The occurrence of high densities of ruminant livestock is counter-intuitive considering the extent and continuous nature of cropping on densely populated islands such as Java where little land remains suitable for grazing. As a consequence, livestock are permanently housed in backyards and fed indigenous forages cut from field margins and roadsides. Although cut-and-carry feeding is labour-intensive, it is surprising that farmers collect quantities of forage greatly in excess of the requirements of their livestock. In an experiment, indigenous forage was fed to sheep at increasing rates: 25, 50 or 75 g DM kg-' liveweight daily. The results showed that although DM intake and liveweight gain rose with increasing offer-rate, the incremental improvements from 50 to 75 were non-significant (p<0.05) and <25 to 50. It is unlikely that farmers justify their excess-feeding strategies on the basis of these marginal gains in animal productivity alone. The rationale for excess-feeding also lies in the production of manure-composts. Group-interviews, involving preference-ranking and matrix scoring exercises, indicated that in upland areas, farmers have an extensive knowledge regarding organic fertiliser quality and use. Farmers place value on the inclusion of animal wastes, particularly urine, into composts. In rain fed areas, manure production ranked similar to meat production in importance as outputs from the sheep enterprise. The research demonstrates how livestock are traditionally used to produce high quality compost and provides evidence to support the hypothesis that integration of livestock into Javanese agriculture is essential to sustaining some of the world's most intensive smallholder farming systems.